How to manage R & D in uncertain environments - Nuria Rodríguez-López; Beatriz González-Vázquez; Elena Rivo-López (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
The benefits of doing R & D activities have been unanimously stated in the academic literature. Although a clear answer on what is the best way to manage these activities has not yet been reached. This lack of definition is exacerbated in uncertain environments where it is difficult to predict future developments. The purpose of this paper is to obtain a single answer on whether to integrate R & D in uncertain environments. To do this we use a multisectoral sample. The results obtained allow us to reject full integration strategies in favor of those other strategies based on the participation of external agents.
Keywords: 650; R&D; integration; market uncertainty; technology uncertainty